CIPCA (crisis intervention program for children and adolescents) preventing posttraumatic psychopathology - Ahmad, Abdulbaghi (Henry Stewart Talks, 2018)
CIPCA (crisis intervention program for children and adolescents) preventing post-traumatic psychopathology: aims, structure, function and instruments, Metin health house, CIPCA pilot project